Geochemical Characteristics of B-Li-Cl Type Waters in Geothermal Area: Implications for the Origin of Tawau Hot Springs, Sabah, Malaysia - Fredolin Javino; Ignatius Adi Prabowo; Mohd Rashidi Abdull Manap; Norizah Abdul Rahman (International Journal of Hydrological and Environmental for Sustainability, 2024)
Boron (B), Lithium (L), and Chlorine (Cl) are valuable indicators in geothermal detection due to their unique properties and behavior in hydrothermal systems. Volcanic hot springs are generally believed to originate from meteoric circulation or buried seawater and are controlled by equilibrium exchange with magmatic rocks at high temperatures. In this study, we report the B-Li-Cl geochemical characteristics of Tawau hot springs, in the forearc region of Malaysia. The data has been collected from previous studies that analyzed 8 water samples to determine the levels of 10 dissolved elements or components. We performed data correlation analyses to infer the source materials and origins of the hot springs. In addition, we performed numerical modeling of oxygen and hydrogen isotope fractionation to examine the composition of derived fluids as possible candidates of geofluids. The results suggest that Tawau geothermal originated from deep seawater due to subduction before undergoing magmatisation and alteration processes. This interpretation result has a positive correlation with Li and boron. In addition, the geological conditions in the Sabah region, which has subduction zones from two directions, cause a high probability of seawater or marine sediment contribution into the reservoir before finally coming out in the form of a geothermal fluid phase.